PROJECT METHOD AS A MEANS OF FORMATION OF COMPETENCIES OF FUTURE PROFESSIONALS IN HOTEL AND RESTAURANT BUSINESS IN THE PROCESS OF ECOLOGY STUDIES - Tetiana I. Yusypiva; Halyna I. Miasoid (Alfred Nobel University Publisher, 2021)
Peculiarities of application of the project method for general and special competencies formation of future Hospitality specialists are studied. It is revealed that training of ecological practices in the system of vocational education should be based on the subject biological competences, take into account psychological features of late adolescence of first-year students, meet the requirements of level 6 of the National Qualifications Framework and ensure the formation of learning outcomes of Bachelor's programme 'Hotel & Restaurant Business' at Alfred Nobel University. The authors' methodical material is presented, an educational project on the analysis and improvement of sustainable practices in hospitality, aimed at the formation of a number professional competencies. It is established that the chosen learning methods allow students to do their research and work within student autonomy, establish interaction in teams, develop skills of argumentation and critical thinking, present the obtained results of work, be responsible for decisions and results of their cooperation concerning topical issues of future professional activity. The role of the lecturer is to develop a project methodology, formulate clear instructions for project implementation and the assessment system, provide support and facilitation. To work on the project, students independently divided their group into small groups of 4-5 team members each. Each group was given the task to develop a project 'Environmental practices in the hotel and restaurant business' on the example of a hospitality facility, outlining the prospects for the development of hotel and restaurant business in Ukraine as a type of environmental services, the concept of the studied eco-hotel, used energy saving technologies, greening of the exterior and interior, the features of accommodation and food for ecotourists. Moreover, suggestions as for optimisation of the sustainable practices or their introduction of the analysed hotel had to be given and justified. The search work of the applicants and their development of the project included brainstorming and presentation of ideas; distribution of responsibilities in the group; research; development of students' own proposals for greening the hotel; compiling a synopsis (text) of the work; preparing and delivering a multimedia presentation. The quantitative method allowed to distinguish the levels of student general and special competencies formation: 20% and 30% of students had average and sufficient levels accordingly, and 46% showed high level. By applying qualitative method, it was found, that project work in the course of Ecology increases the efficiency of general and special competencies formation of Bachelors in Hotel & Restaurant Business, student satisfaction with the forms of class organization, learning methods and students' interest in obtaining ecological knowledge.